(untitled) (Revista de Ciências Agroveterinárias, 2019)
Common bean landraces represent heterogeneous, local adaptations of domesticated species, and thereby provide genetic resources that meet current and new challenges for farming. These local ecotypes can show variable phenology and low-to-moderate edible yield, however, they are highly nutritious. Therefore, strategies to stimulate the conservation of this genetic diversity are important. The maintenance of seed germination potential is also an important feature in the characterization of genetic diversity to conserve biodiversity. The main objective of this study was to discriminate common bean landrace cultivars available at Santa Catarina State University (UDESC) germplasm bank according to their seed physiological diversity and agronomic parameters (germination rate, viability, seed vigor, and seedling growth) and based on Mulamba and Mock selection index. There is a large physiological diversity in common bean landrace cultivars. BAF 112 and BAF 81, BAF 84, BAF 42, BAF 60, and BAF 75, were identified as more promising for the storage of the seeds under conventional conditions, being able to maintain the viability and vigor during storage. Mulamba and Mock selection index were capable of selecting superior cultivars with high physiological quality.